The Amoraic controversy, halakha and authority in Bavli Eruvin 104a - Zur, Uri (HTS teologiese studies, 2021)
The Talmud Bavli presents in Tractate Eruvin (104a) a controversy between two Amoraim, Ulla and Rabbah. This controversy on the topic of producing a sound on the Sabbath is the context of the present study. According to Ulla, any production of sound on the Sabbath is forbidden, and according to Rabbah, producing a musical sound is prohibited on the Sabbath but producing a sound that is not musical is permitted. The purpose of the study is to present the two approaches to solving the controversy, where the dilemma is which of them should the halakha follow. The setting of the study is a comparative analysis of two different halakhic approaches. Accordingly, this controversy created two different fundamental halakhic approaches that have implications for the authority of the Talmud Bavli compared to the Talmud Yerushalmi, that is, which of these Talmuds has more authority than the other. The research methods of this article portray the various outlooks of the poskim and commentators, from amongst the first representatives to relate to this problem, where the results show that a relative majority of the commentators follow the approach of the Rif. The article’s conclusion is that the authority of the Talmud Bavli is greater than that of the Talmud Yerushalmi.Contribution: The contribution of the article is in showing the fundamental arguments that the poskim and commentators raised to solve this dilemma, which serve as a basic foundation for all the poskim and commentators who followed them and who advocated either the one approach or the other. Furthermore, the article also contributes by providing a source interpretation of the Hebrew and Aramaic text and rabbinic literature, which fits the scope of the journal.